Perception of COVID-19 Pandemic by Brazilian People With Parkinson’s Disease and Multiple Sclerosis - Simieli, Lucas; Santinelli, Felipe B.; Costa, Elisa C.; Kuroda, Marina H.; Oliveira, Lorena R.; Penedo, Tiago; Pilon, Julia; Silveira, Aline P. B.; Assis, Iramaia S. A.; Tardelli, Erica; Okamoto, Erika; Barbieri, Fabio A. (Frontiers in Psychology, 2022)
COVID-19 in Brazil is threatening, and it has forced the government to adopt partial lockdown as a strategy to stop the spread of the virus in the first wave of pandemic (March 2020). These preventive measures during the COVID-19 pandemic may affect the motor and non-motor symptoms in people with Parkinson’s disease (PD) and Multiple sclerosis (MS). Thus, the purpose of this study was to investigate the perception during the first wave of COVID-19 pandemic lockdown on motor and non-motor symptoms, and also measure physical activity level, quality of life, and sleep quality in Brazilian people with PD and MS. One hundred and fifty-three participants (PD-97 and MS-56) answered an online survey to identify the perception of motor and non-motor symptoms, and characterize the physical activity level, and quality of life and sleep in these neurological Brazillian population. During the beginning of pandemic lockdown in Brazil, our results indicated that 69% of people with PD and 55% of people with MS reported worse on motor aspects and lower amount of physical activity performed. Also, 75.2% (PD) and 92.9% (MS) of our cohort were considered inactive or sedentary. Based on the perception and behavior of the population studied, people with PD and MS should be encouraged to perform more physical activity in order to reduce the effects of isolation in motor and non-motor aspects of the diseases. Teleinterventions, such as home-based exercise, should be included in the new routine of people with PD and MS to reduce the impacts of lockdown and to maintain quality of life at a good level.